Analisis Kontekstual atas Tafsir Departemen Agama Republik Indonesia - Muhammad Iqbal; Syauqi Aulade Ghifari (UIN Sunan Gunung Djati Bandung, 2022)
This study purpose to explore Indonesian Tafsir, especially the tafsir issued by the Indonesian government. The method used in this research is a qualitative research method with a descriptive analytical approach through data collection by literature study. The results obtained from this study are that the official Tafsir issued by the Government of Indonesia, in this case issued by the Ministry of Religion, aims to facilitate the Indonesian people in the need to study the Qur'an from the beginning from the issuance of the Al-Qur’an Translation product to the thematic interpretation product. This research is expected to be a treasure trove of knowledge among the community, especially for researchers who focus on the Tafsir Nusantara research.